FACTORS DETERMINING THE RELATIONSHIP BETWEEN SUPERIORS AND THEIR SUBORDINATES: EVALUATING THE TRUST FACTOR IN CHINESE ORGANIZATIONS - Law, Kian Aun L (International Journal of Psychosocial Rehabilitation, 2020)
When it comes to the characteristics of superior behavior in trust development orientation, it includes five dimensions: guidance behavior, fair behavior, control sharing, integrity behavior and superior competence behavior; on the contrary, the features of subordinate behavior consists of four levels, namely,prudent behavior, loyal behavior, integrity behavior and subordinate competence behavior. This paper, proves that emotional trust has influence on employee’s behavior and performance, including direct and indirect effects, which means that on the one hand, emotional trust imposes direct impact on employee’s task performance and individual citizenship behavior, the mediating role via emotional trust on the other hand plays indirect role in employee’s performance and organizational citizenship behavior. The last part is the conclusion of the whole paper, and reveals the weakness of the study and the future research orientation at the same time.